Plan de negocios para la creación de una empresa de servicios de limpieza a domicilio - Reinoso Cáceres, Freddy Eduardo (2018)
A decade ago, domestic workers were a very important aid in household activities, but unfortunately the current labor legislation in force has made the vast majority of families decide not to have domestic employees, since this implies a large mployer responsibility, too many contingencies and a high cost that a modern family cannot maintain. This project provides a solution alternative in the topics of home cleaning to modern families, without having to maintain a relationship of dependence a person to perform these activities. Chua is the solution in cleaning activities at home because it is created with the purpose of inspiring honesty and trust in our services with opportunity and flexibility. By taking care of these activities, the family will enjoy additional quality time for the care of their children to maintain a harmonious and healthy coexistence with all its members. With comfortable prices in flexible schedules and with a great differentiator, as is the highly competent staff, guarantees security and confidence to our customers; strategies that lead us to achieve the market, administrative and financial objectives, making this business plan viable.